大學生教育抱負與職業抱負之縱貫性研究 A Longitudinal Study of Educational Aspirations and Occupational Aspirations Among College Students - 張德勝 Te-Sheng Chang; 王鴻哲 Hung-Che Wang; 陳上迪 Shang-Ti Chen (National Taiwan Normal University, 2022)
本研究旨在探討大學生在大學四年之教育抱負與職業抱負的改變情形，並分析性別與就讀領域對這兩種抱負影響的情形。本研究以1,090位大學生為對象，以四次的自填式問卷為工具，持續追蹤其大一至大四教育抱負與職業抱負的成長軌跡，以及性別與就讀領域對於抱負起始狀態及成長速率的影響。本研究採用階層線性分析模式，結果顯示：一、對於教育抱負與職業抱負的發展皆有相同的趨勢，大學生的教育抱負在大一至大三時逐漸下降，大四則有些微上升。二、性別與就讀領域的不同，會造成大學生在起始狀態中教育抱負的差異化，研究顯示男大一生的教育抱負顯著高於女大一生，理工領域大一生的教育抱負顯著高於人文社會領域大一生，但在職業抱負的初始狀態，性別與就讀領域並不會造成其差異。三、性別與就讀領域的差異不會造成教育抱負與職業抱負在成長速率的影響。依據上述分析結果，本研究提出對教育實務及未來研究的建議。 Background The universalization of higher education has presented college graduates with challenges related to underemployment and insufficient compensation. Understanding how the educational and occupational aspirations of college students develop is crucial to developing career counseling programs to help such students succeed in the competitive job market. Most studies of the educational and occupational aspirations of college students in Taiwan have relied on cross-sectional data. Cross-sectional studies assess variables at specific time points and are prone to biases because they cannot determine how variables change over time. Therefore, the current study explored how the educational and occupational aspirations of college students change over the 4 years of college study. Literature Review Aspirations are life goals that are often influenced by personal and social values (Wolbers et al., 2011). Research on social education has categorized aspirations into educational and occupational aspirations (Teravainen-Goff et al., 2020). Educational aspirations refer to educational desires or goals; occupational aspirations refer to occupational preferences and goals regarding future occupational roles (Hauser et al., 1983). Educational and occupational aspirations may change over the 4-year college period (Sharf, 2006). According to Gottfredson (1981), gender and academic field may influence the development of aspirations among college students. In sum, the current study examined the development trajectories of the educational and occupational aspirations of students from their first year to the fourth year of college as well as the effects of gender and academic field on aspiration development. Methods Stratified and purposive sampling was employed to select participants from different types of colleges (both national and private colleges) and academic fields (both science/technology/ engineering and social sciences/humanities). A total of 1,090 first-year students from 11 colleges agreed to share their educational and occupational aspirations via self-report questionnaires in 2011. These participants agreed to fill out follow-up questionnaires between March and May in 2012, 2013, and 2014. To assess the students' educational aspirations, this study asked, "What kind of degree will you want to pursue?" (Chen & Hwang, 2011). The responses were coded as 16, 18, and 22 for a bachelor's, master's, or doctoral degree. Hwang's (2008) improved Taiwanese occupational prestige and socioeconomic status scale was used to measure the participants' occupational aspirations. The participants were provided with a list of jobs (e.g., administrative assistant, teacher, or technician) and asked to select one. The jobs were assigned continuous numerical values based on those used by Hwang (2008). Two-level hierarchical linear modeling (HLM) was conducted for assessing the development of educational and occupational aspirations over the 4 years. Additionally, the moderating effects of gender and academic fields on the development of educational and occupational aspirations were examined using statistical tests performed in HLM 7.0. Results The two-level HLM revealed the following results: First, both educational and occupational aspirations exhibited similar development trends: a linear decline from the first year to the third year followed by a linear increase in the final year. Second, differences in gender and academic field affect educational aspirations initially; specifically, educational aspirations among male first-year students were higher than those among female first-year students. Also, first-year students in the fields of science, technology, and engineering had higher educational aspirations than those in the fields of social sciences and the humanities. However, gender and academic field did not initially affect occupational aspirations. Finally, neither gender nor academic field affected the development of educational or occupational aspirations in the later years of college. Discussion and Suggestions Consistent with prior studies (Chen & Hwang, 2011; Pramod, 2021), the current study discovered that first-year students had the highest educational and occupational aspirations. The students' aspirations gradually decreased and were the lowest during their third year of study. A potential explanation for this finding is that students tend to be idealistic when starting college. However, they begin to realize that their actual academic performance may not be as high as they expected, reducing their aspirations in their third and fourth years of study. In line with previous studies (Gottfredson, 1981; Teravainen-Goff, 2020; Wang, 2007), this study discovered that first-year students who were female or in the fields of social sciences or the humanities had lower educational aspirations than their counterparts who were male or in the fields of science, technology, or engineering. The gender-based difference in aspirations may be attributed to the social norms in Taiwan. Taiwanese society holds some negative stereotypes regarding women who completed advanced degrees. The difference in aspirations owing to the academic field may be explained by the fact that science, technology, and engineering students are expected to pursue higher education to prepare for rapid changes in technology. The results imply three suggestions for educational practitioners. First, focused counseling programs suitable for students in each year of college should be organized. Second, gender-equal education should be encouraged to bridge the gap between the aspirations of male and female students. Finally, career guidance focused on specific academic fields should be implemented early in students' college careers to help them establish informed educational and occupational aspirations and accordingly develop their skills to excel in their respective academic and professional fields.